Carrier Dynamics in Alloyed Chalcogenide Quantum Dots and Their Light‐Emitting Devices. Issue 40 (15th September 2021) - Li, Zhaohan; Wei, Jing; Wang, Fangfang; Tang, Yanan; Li, Anming; Guo, Yating; Huang, Pan; Brovelli, Sergio; Shen, Huaibin; Li, Hongbo
Abstract: Light‐emitting devices based on alloyed quantum dots have reached external quantum efficiencies above 20% in red, green, and blue emission devices. Their outstanding performances including high efficiency, long‐term device stability, and suppressed efficiency roll‐off identify alloyed‐quantum‐dot based light‐emitting devices as good candidates for next generation solid‐state lightings and displays. All these advantages stem from the chemical composition gradient of alloyed quantum dots in radial direction. The chemical composition gradient enables the lattice strain to be released gradually, eventually decreasing interface defects and suppressing Auger recombination. Carrier dynamics play a crucial role in the fundamental properties and functionalities of quantum dots for solid‐state devices and light‐emitting devices. A more in‐depth understanding of carrier dynamics in quantum dots is therefore of both fundamental and technological significance. This review article provides an overview on recent advances in the study and understanding of carrier dynamics of alloyed quantum dots and alloyed‐quantum‐dot based light‐emitting devices. Particular emphasis is placed on the relationship between Auger recombination and optical properties and optoelectronic properties. This review is expected to encourage further research in alloyed quantum dots and related devices and to stimulate new synthesis efforts to produce stable alloyed quantum dots with further improved control of carrier dynamics. Abstract : Carrier dynamics plays a crucial role in the fundamental properties and functionalities of quantum dots for solid‐state devices and light‐emitting devices. An overview of carrier dynamics in alloyed quantum dots and their light‐emitting devices is provided, in the hope of encouraging further research in alloyed quantum dots and related devices.